Efektivitas Kunjungan Lapangan untuk Materi Berbagai Pekerjaan di Pelajaran IPS Kelas 4 - Alifia Mutsla Fakhruddin; Putri Rizqi Tanzila Sudirman; Tin Rustini; Yona Wahyuningsih (Journal on Education, 2023)
This study aims to determine the effectiveness of field visits in various jobs in social studies learning, because they should acquire knowledge in understanding different social environments at different places and times, both individually and in groups to find their interests which can ultimately form a good community environment. And harmonious. There are three objectives for the achievement of social studies learners, namely; The first is the development of students’ intellectual abilities, the second is the development of the ability to sense responsibility as members of the community and citizens, and the third is as a student’s personal developer